Teknik Dehidrasi Osmosis Pada Pembuatan Manisan Kulit Jeruk - Teuku Augibran Givari; La Choviya Hawa; Angky Wahyu Putranto (Politeknik Negeri Jember, 2022)
High consumption of oranges (Citrus sinensis) leads to the increase of orange peel waste, that’s why those orange peel waste needs to be utilized as a value-added product, such as fruit candy. Fruit candy can be produced by a process called osmotic dehydration, which is the process of immersing food material in a hypertonic solution. This research was done with Randomized Block Design to understand the effect of immersion time (2, 4, and 6 hours) and blanching time as the pretreatment (2,5, 5, and 7,5 minutes). This research was done in triplicate. The parameters that were observed are solid gain (SG), water loss (WL), weight reduction (WR), water content, and colors (L*, a*, and b*). The results indicated that the increase in immersion and blanching time causes the value of solid gain (SG) and water loss (WL) to increase, weight reduction to decrease then increase, and water content to decrease. Analysis of Variance test suggests that immersion time has a significant effect on SG, WL, WR, water content, L*, and a*. On the other hand, blanching time only significantly affects SG, WL, WR, and water content. According to Multiple Attribute Utility Theory, the best treatment in this research, regarding the results of SG, WL, WR, and water content, is the treatment with 6 hours immersion time and 7,5 minutes blanching time.